Deciphering Bacterial Chemorepulsion: The Complex Response of Microbes to Environmental Stimuli - Fu, Ruixin; Feng, Haichao (Microorganisms (Basel), 2024)
Bacterial motility relying on flagella is characterized by several modes, including swimming, swarming, twitching, and gliding. This motility allows bacteria to adapt remarkably well to hostile environments. More than 50% of bacteria naturally contain flagella, which are crucial for bacterial chemotaxis motility. Chemotaxis can be either positive, where bacteria move towards a chemical source, or negative, known as chemorepulsion, where bacteria move away from the source. Although much is known about the mechanisms driving chemotaxis towards attractants, the molecular mechanisms underlying chemorepulsion remain elusive. Chemotaxis plays an important role in the colonization of the rhizosphere by rhizobacteria. Recently, researchers have systematically studied the identification and recognition mechanisms of chemoattractants. However, the mechanisms underlying chemorepellents remain unclear. Systematically sorting and analyzing research on chemorepellents could significantly enhance our understanding of how these compounds help probiotics evade harmful environments or drive away pathogens.